On Existence of Sequences of Weak Solutions of Fractional Systems with Lipschitz Nonlinearity. (12th March 2021) - Guefaifia, Rafik; Boulaaras, Salah Mahmoud; El-Sayed, Adel Abd Elaziz; Abdalla, Mohamed; Cherif, Bahri-Belkacem
Abstract : In this article, the variational method together with two control parameters is used for introducing the proof for the existence of infinitely many solutions for a new class of perturbed nonlinear system having p -Laplacian fractional-order differentiation.